2006
DOI: 10.1074/jbc.m602099200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of cGMP-dependent Protein Kinase Expression by Rho and Krüppel-like Transcription Factor-4

Abstract: Type I cGMP-dependent protein kinase (PKG I) plays a major role in vascular homeostasis by mediating smooth muscle relaxation in response to nitric oxide, but little is known about the regulation of PKG I expression in smooth muscle cells. We found opposing effects of RhoA and Rac1 on cellular PKG I expression: (i) cell density-dependent changes in PKG I expression varied directly with Rac1 activity and inversely with RhoA activity; (ii) RhoA activation by calpeptin suppressed PKG I, whereas RhoA down-regulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 74 publications
0
35
0
Order By: Relevance
“…KLFs are a subclass of evolutionarily conserved transcription factors [28] and KLF4 expression is associated with growth arrest and the inhibitory effect of SMC marker expression [29]. Previous studies have demonstrated that KLF4 potently represses expression of multiple SMC genes by repressing MyoCD levels during phenotypic switching of SMC in response to vascular injury, transforming growth factor-b, or platelet-derived growth factor-BB [14][15][16][30][31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…KLFs are a subclass of evolutionarily conserved transcription factors [28] and KLF4 expression is associated with growth arrest and the inhibitory effect of SMC marker expression [29]. Previous studies have demonstrated that KLF4 potently represses expression of multiple SMC genes by repressing MyoCD levels during phenotypic switching of SMC in response to vascular injury, transforming growth factor-b, or platelet-derived growth factor-BB [14][15][16][30][31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…For PKG, prolonged activation fosters autophosphorylation, which has been shown to promote ubiquitination and protein breakdown (Dey et al, 2009). PKG expression is also down-regulated by RhoA and up-regulated by Rac1, but whether these processes are in play with prolonged elevation of cGMP is not known (Zeng et al, 2006). These changes in PDEs and PKG in response to sustained increases in the NO/ cGMP/PKG signaling pathway suggest a classic feedback response to blunt or terminate a signal.…”
Section: B Persistent Effects Of Nitric Oxide/cgmp Signalingmentioning
confidence: 99%
“…Quantitative Reverse Transcription-PCR-One microgram of total cytoplasmic RNA was subjected to reverse transcription with random hexamer primers, and quantitative PCR was performed using an Mx3000 real time PCR detection system (Stratagene) with IQ TM SYBR Green Supermix (Bio-Rad) (22). The following primers were used: 5Ј-GACCAGCCTTTTCA-CAGCTC-3Ј (AAF-44, sense) and 5Ј-GCAAGGGACAG-CAAAGACTC-3Ј (AAF-44, antisense) and 5Ј-AACGGAT-TTGGTCGTATTGGG-3Ј (glyceraldehyde-3-phosphate dehydrogenase, sense) and 5Ј-TGGAGGATGGTGATGGGAT-TTC-3Ј (glyceraldehyde-3-phosphate dehydrogenase, antisense).…”
Section: Methodsmentioning
confidence: 99%